Regional initiatives to address the challenges of tuberculosis in children: perspectives from the Asia-Pacific region. (March 2015) - Graham, Stephen M.; Grzemska, Malgorzata; Brands, Annemieke; Nguyen, Huong; Amini, James; Triasih, Rina; Talukder, Khurshid; Ahmed, Shakil; Amanullah, Farhana; Kumar, Blessina; Tufail, Pervaiz; Detjen, Anne; et al.
Highlights: We highlight recent global progress on attention to the neglected disease of tuberculosis in children and adolescents. We provide reasons for previous neglect and rationale for why this must change as part of post-2015 global tuberculosis control strategy. We highlight recent regional and national initiatives that aim to improve diagnosis, management, outcomes and prevention for children with tuberculosis in the Asia-Pacific region. We stress that strong collaborative efforts between the child health sector, the community and the NTP, and led by local child TB champions, are essential to improve the care of children and address persistent policy-practice gaps. Abstract: Increasing attention is being given to the challenges of management and prevention of tuberculosis in children and adolescents. There have been a number of recent important milestones achieved at the global level to address this previously neglected disease. There is now a need to increase activities and build partnerships at the regional and national levels in order to address the wide policy-practice gaps for implementation, and to take the key steps outlined in the Roadmap for Child Tuberculosis published in 2013. In this article, we provide the rationale and suggest strategies illustrated with examples to improve diagnosis, management, outcomes and prevention for children with tuberculosis in the Asia-Pacific region, with an emphasis on the need for greatly improved recording and reporting. Effective collaboration with community engagement between the child health sector, the National Tuberculosis control Programmes, community-based services and the communities themselves are essential.